(untitled) - Stewart, Elizabeth A. (New York, 2000)
Exploring Twins presents an analysis of twinship considered as a specifically social phenomenon. Drawing upon a wide range of interdisciplinary, historical and cross-cultural data, Elizabeth A. Stewart argues that in both traditional and modern societies, twinship represents a recurrent anomaly which calls into question the assumptions around which different types of society are organized. Part I identifies and analyzes the fascinating range of cultural and disciplinary approaches to the interpretation of twinship, while Part II considers the possibilities for a distinctively social analysis of twinship.
Keywords: Twins